2019
DOI: 10.3389/frobt.2019.00134
|View full text |Cite
|
Sign up to set email alerts
|

Symbol Emergence as an Interpersonal Multimodal Categorization

Abstract: This study focuses on category formation for individual agents and the dynamics of symbol emergence in a multi-agent system through semiotic communication. Semiotic communication is defined, in this study, as the generation and interpretation of signs associated with the categories formed through the agent's own sensory experience or by exchange of signs with other agents. From the viewpoint of language evolution and symbol emergence, organization of a symbol system in a multi-agent system (i.e., agent society… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…multimodal concept formation) have a strong relationship [1,64,65]. 3 Figure 2 depicts the overview of a symbol emergence system (SES) which is the core concept of symbol emergence in robotics [64,71]. The theory of SES argues that semiotic communication should be based on embodied environmental adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…multimodal concept formation) have a strong relationship [1,64,65]. 3 Figure 2 depicts the overview of a symbol emergence system (SES) which is the core concept of symbol emergence in robotics [64,71]. The theory of SES argues that semiotic communication should be based on embodied environmental adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding symbol emergence systems based on multimodal sensory information, the following three questions arise that have not been verified in previous works [5][6][7]:…”
Section: Introductionmentioning
confidence: 89%
“…Hagiwara et al proposed a computational model of a symbol emergence system comprising two agents that perform categorization based on a visual modality, i.e., a single modality [5]. We call the model proposed in [5] interpersonal Dirichlet mixture (Inter-DM) in this study because the model is obtained by combining two Dirichlet mixtures (DMs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we consider that the integration of the MLDA and representation learning is also significant in terms of leveraging past research. Although pre-designed or pre-trained feature extractors have been used, various studies (Attamimi et al, 2014;Nakamura and Nagai, 2017;Hagiwara et al, 2019;Miyazawa et al, 2019) in addition to the above have revealed the effectiveness of the MLDA for multimodal concept formation. That is, the integration of the MLDA and representation learning makes it possible to develop these studies further.…”
Section: Introductionmentioning
confidence: 99%